Attitudes of the Ecuadorian University Community Toward Genetically Modified Organisms - Román Collazo, Carlos; Chacha Guerrero, Karen; Loja Mejia, Tatiana; Andrade Campoverde, Diego; Hernández Rodriguez, Yenima (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: The acceptance of Genetically Modified Organisms (GMOs) by the civilian population in Ecuador is a controversial issue, where beliefs and practices are determinants. In Ecuador, the use of GMOs for research or productive purposes has been banned since 2008; however, the current position of the population towards this technology is unknown. Objective: To explain the attitude towards GMOs in the Ecuadorian university population based on sociodemographic variables, knowledge, beliefs, practices, and bioethical approach. Methods: A validated survey was applied to 719 students and teachers of the Catholic University of Cuenca through google forms. The collected data were processed using the SPSS 23.0 software. Multivariate and linear regression analysis was used to explain the attitude towards GMOs based on the variables studied. Results: Partial approval of GMO use is research-oriented, with a rejection towards food. The linear regression model explained 65 % of the variance of Attitude towards GMOs from the Beliefs, Practices, Knowledge, and Bioethical approach variables. The sociodemographic variables were completely excluded from the model due to the absence of statistical significance. Conclusions: The incipient acceptance of GMOs in the academic sector corroborates a transformation in the thinking of Ecuadorian civil society. Considerations on the use of GMOs are supported by a bioethical approach that leans towards a pragmatic utilitarianism based on the immediate or mediates benefits of the technology.